2014
DOI: 10.14260/jemds/2014/3386
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Midazolam -Thiopentone With Propofol on Laryngeal Mask Airway Insertion Condition

Abstract: BACKGROUND AND AIMS: Laryngeal mask airway (LMA), an alternative airway device, provides and maintains a seal around the laryngeal inlet for spontaneous ventilation as well as modest level of positive pressure ventilation. But LMA requires a sufficient depth of anaesthesia& depression of airway reflexes to avoid adverse reactions like gagging, coughing, head & limb movements etc. We intended to test the efficacy of Thiopentone and Midazolam combination as an effective alternative to Propofol for insertion of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…The two groups were comparable in age, gender, weight, ASA physical status, and MPS. This finding was similar to various other studies [ 5 , 14 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…The two groups were comparable in age, gender, weight, ASA physical status, and MPS. This finding was similar to various other studies [ 5 , 14 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…Statistically, a significant difference was found in falls in heart rate and various blood pressure levels between the groups. Concluded that propofol at a rate of 2.5 mg/kg was found to be superior to thiopentone at a rate of 5 mg/kg as far as suppression of upper airway reflexes in LMA insertion which is in correlation with other studies [15][16][17].…”
Section: Apparao Et Alsupporting
confidence: 56%
“…[ 17 18 ] Numerous studies have shown that midazolam compared to thiopental in people with underlying disease has better hemodynamic stability. [ 7 19 20 ]…”
Section: Introductionmentioning
confidence: 99%